Venipuncture-Induced Complex Regional Pain Syndrome: A Case Report and Review of the Literature - Foad Elahi; Chandan G. Reddy (Case Reports in Medicine)
Venipuncture, the most frequently performed invasive medical procedure, is usually benign. Generally it produces only transitory mild discomfort. Venipuncture-induced neuropathic pain is hard to recognize at an early stage. Medical literature reviews show that there is not adequate medical knowledge about this important subject. The inciting incident in complex regional pain syndrome (CRPS) can often seem far too trivial to result in a condition with such severe pathophysiologic effects. The practicing physician has little information available to enable early recognition of the condition, initiation of multidisciplinary treatment modalities, and proper referral to pain specialists. We encountered a unique case of venipuncture-induced complex regional pain syndrome (CRPS). The patient is a 52-year-old school teacher with no significant past medical history, who presented initially to the Center of Pain Medicine with left upper extremity pain. The pain started while phlebotomy was performed in the patient’s left antecubital area for routine blood check. The patient’s pain did not improve with multiple medications, physical therapy, or several nerve blocks. The patient demonstrated all the signs and symptoms of chronic neuropathic pain of CRPS in the upper extremity with minimal response to the continuous pain management. We decided to proceed with cervical spinal cord nerve stimulation along with continuing other modalities. The patient responded to this combination. During the follow-up, we noticed that the patient’s pain course was complicated by extension of the CRPS to her lower extremity. We will describe the course of treatment for the patient in this paper. In this paper we will discuss the electrical neuromodulation as an important modality in addition to the multidisciplinary pain management for a patient with venipuncture-induced chronic neuropathic pain.